ТРАГЕДИЯ ЖАНРЫНДА СЮЖЕТ ҲӘМ КОНФЛИКТ (К.Рахмановтың «Жаралы жүреклер» трагедиясы тийкарында) - Шержанова, Ф.К. (FAN va JAMIYAT, 2019)
The article presents information about Karakalpak dramaturgy. It tells about the musical drama “Injured hearts” by K.Pakhmanov which was staged at Karakalpak state academic theatre. The author discusses about the characters in the drama. The skill of the dramatist on creating characters are shown with the help of examples.